Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 188192 by universe last updated on 26/Feb/23

         prove that       ∫_0 ^∞ e^(−a^2 x^2 ) cos(2bx) dx   =   ((√π)/(2a))e^(−b^2 /a^2 )

$$\:\:\: \\ $$$$\:\:\:\:{prove}\:{that} \\ $$$$\:\:\:\:\:\int_{\mathrm{0}} ^{\infty} {e}^{−{a}^{\mathrm{2}} {x}^{\mathrm{2}} } \mathrm{cos}\left(\mathrm{2}{bx}\right)\:{dx}\:\:\:=\:\:\:\frac{\sqrt{\pi}}{\mathrm{2}{a}}{e}^{−{b}^{\mathrm{2}} /{a}^{\mathrm{2}} } \\ $$$$ \\ $$$$ \\ $$

Answered by qaz last updated on 26/Feb/23

I(b)=∫_0 ^∞ e^(−a^2 x^2 ) cos (2bx)dx  I(b)′=−∫_0 ^∞ 2xe^(−a^2 x^2 ) sin (2bx)dx=(1/a^2 )e^(−a^2 x^2 ) sin (2bx)∣_0 ^∞ −((2b)/a^2 )∫_0 ^∞ e^(−a^2 x^2 ) cos (2bx)dx  ⇒I(b)′=−((2b)/a^2 )I(b)           ⇒I(b)=Ce^(−(b^2 /a^2 ))   C=I(0)=∫_0 ^∞ e^(−a^2 x^2 ) dx=((Γ((1/2)))/(2(a^2 )^(1/2) ))=((√π)/(2a))    ,a>0  ⇒I(b)=((√π)/(2a))e^(−(b^2 /a^2 ))      ,a>0

$${I}\left({b}\right)=\int_{\mathrm{0}} ^{\infty} {e}^{−{a}^{\mathrm{2}} {x}^{\mathrm{2}} } \mathrm{cos}\:\left(\mathrm{2}{bx}\right){dx} \\ $$$${I}\left({b}\right)'=−\int_{\mathrm{0}} ^{\infty} \mathrm{2}{xe}^{−{a}^{\mathrm{2}} {x}^{\mathrm{2}} } \mathrm{sin}\:\left(\mathrm{2}{bx}\right){dx}=\frac{\mathrm{1}}{{a}^{\mathrm{2}} }{e}^{−{a}^{\mathrm{2}} {x}^{\mathrm{2}} } \mathrm{sin}\:\left(\mathrm{2}{bx}\right)\mid_{\mathrm{0}} ^{\infty} −\frac{\mathrm{2}{b}}{{a}^{\mathrm{2}} }\int_{\mathrm{0}} ^{\infty} {e}^{−{a}^{\mathrm{2}} {x}^{\mathrm{2}} } \mathrm{cos}\:\left(\mathrm{2}{bx}\right){dx} \\ $$$$\Rightarrow{I}\left({b}\right)'=−\frac{\mathrm{2}{b}}{{a}^{\mathrm{2}} }{I}\left({b}\right)\:\:\:\:\:\:\:\:\:\:\:\Rightarrow{I}\left({b}\right)={Ce}^{−\frac{{b}^{\mathrm{2}} }{{a}^{\mathrm{2}} }} \\ $$$${C}={I}\left(\mathrm{0}\right)=\int_{\mathrm{0}} ^{\infty} {e}^{−{a}^{\mathrm{2}} {x}^{\mathrm{2}} } {dx}=\frac{\Gamma\left(\frac{\mathrm{1}}{\mathrm{2}}\right)}{\mathrm{2}\left({a}^{\mathrm{2}} \right)^{\frac{\mathrm{1}}{\mathrm{2}}} }=\frac{\sqrt{\pi}}{\mathrm{2}{a}}\:\:\:\:,{a}>\mathrm{0} \\ $$$$\Rightarrow{I}\left({b}\right)=\frac{\sqrt{\pi}}{\mathrm{2}{a}}{e}^{−\frac{{b}^{\mathrm{2}} }{{a}^{\mathrm{2}} }} \:\:\:\:\:,{a}>\mathrm{0} \\ $$

Commented by universe last updated on 26/Feb/23

thanks sir

$${thanks}\:{sir} \\ $$

Answered by ARUNG_Brandon_MBU last updated on 26/Feb/23

Ω=∫_0 ^∞ e^(−a^2 x^2 ) cos(2bx)dx     =(1/2)Re∫_(−∞) ^∞ e^(−(a^2 x^2 +2ibx)) dx     =(1/2)Re∫_(−∞) ^∞ e^(−[a^2 (x+((ib)/a^2 ))^2 +(b^2 /a^2 )]) dx     =(1/2)Re{e^(−(b^2 /a^2 )) ∫_(−∞) ^∞ e^(−(ax+((ib)/a))^2 ) dx}     =(1/2)Re{e^(−(b^2 /a^2 )) (1/a)∫_(−∞) ^∞ e^(−u^2 ) du}=((√π)/(2a))e^(−(b^2 /a^2 ))

$$\Omega=\int_{\mathrm{0}} ^{\infty} {e}^{−{a}^{\mathrm{2}} {x}^{\mathrm{2}} } \mathrm{cos}\left(\mathrm{2}{bx}\right){dx} \\ $$$$\:\:\:=\frac{\mathrm{1}}{\mathrm{2}}{Re}\int_{−\infty} ^{\infty} {e}^{−\left({a}^{\mathrm{2}} {x}^{\mathrm{2}} +\mathrm{2}{ibx}\right)} {dx} \\ $$$$\:\:\:=\frac{\mathrm{1}}{\mathrm{2}}{Re}\int_{−\infty} ^{\infty} {e}^{−\left[{a}^{\mathrm{2}} \left({x}+\frac{{ib}}{{a}^{\mathrm{2}} }\right)^{\mathrm{2}} +\frac{{b}^{\mathrm{2}} }{{a}^{\mathrm{2}} }\right]} {dx} \\ $$$$\:\:\:=\frac{\mathrm{1}}{\mathrm{2}}{Re}\left\{{e}^{−\frac{{b}^{\mathrm{2}} }{{a}^{\mathrm{2}} }} \int_{−\infty} ^{\infty} {e}^{−\left({ax}+\frac{{ib}}{{a}}\right)^{\mathrm{2}} } {dx}\right\} \\ $$$$\:\:\:=\frac{\mathrm{1}}{\mathrm{2}}{Re}\left\{{e}^{−\frac{{b}^{\mathrm{2}} }{{a}^{\mathrm{2}} }} \frac{\mathrm{1}}{{a}}\int_{−\infty} ^{\infty} {e}^{−{u}^{\mathrm{2}} } {du}\right\}=\frac{\sqrt{\pi}}{\mathrm{2}{a}}{e}^{−\frac{{b}^{\mathrm{2}} }{{a}^{\mathrm{2}} }} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com